An Exploratory Discussion of a British Apparel Brand in Relation to New Markets: Developing Actionable Recommendations Based on Network, Relationship, and Collaboration Perspectives - Le Thuy Linh; Hiroko Oe (Budapest International Research and Critics University, 2020)
Marks and Spencer (M&S) is a leading UK fashion retailer. However, the organisation is struggling to improve its domestic operation and to achieve its international objectives, most notably manifest through its withdrawal from China. Through conducting a critical analysis and an evaluation of the supply networks of M&S, the global apparel industry and the Chinese market, this discussion paper aims to propose a new set of strategies for M&S’s re-entry. Based on an analytical discussion, the following actionable recommendations are proposed for the company: (1) to seek suitable network partners in China, (2) to build sustainable relationships with relevant partners to build business strategies based on Chinese consumers’ perspectives and behaviour, and (3) to focus on a new value chain to enhance profitability and sustainability in the new market.